Using video-supported reflection in peer groups to increase instructional effectiveness. Issue 1 (2nd January 2017) - Lebak, Kimberly
Abstract: This article reports upon the findings of research that explored change in teachers' reflective thought and practice on a core set of complex teaching practices after the teachers participated in video-supported reflection model. Five 4th–7th grade teachers participated in the model that paired video-supported collaborative reflection with a research-based observation instrument, Classroom Assessment Scoring System (CLASS). Classroom observation data was collected by video and scored to determine change in teaching practice. All video-supported collaborative dialogue sessions between peers were videotaped and transcribed. Findings point to the developmental process necessary when learning to critically reflect upon and enact complex instructional practices that are not already prominent in practice. Individual development of practice progressed as the collaborative dialogue group expanded their capacity for describing, understanding, and evaluating practice based upon a new schema of effective practice, intentionally enacting change resulting in significant increases in teacher performance.